Molecular mechanisms of viral oncogenesis in haematological malignancies: perspectives from metabolic reprogramming, epigenetic regulation and immune microenvironment remodeling - Qing Xiao; Yi Liu; Xuejiao Shu; Ya Li; Xiaomei Zhang; Chaoyu Wang; Sanxiu He; Jun Li; Tingting Li; Tingting Liu; Yao Liu (Experimental Hematology & Oncology)
Abstract Haematological malignancies are one of the most common tumors, with a rising incidence noted over recent decades. Viral infections play significant roles in the pathogenesis of these malignancies globally. This review delves into the contributions of various known viruses—specifically Epstein-Barr virus (EBV), human immunodeficiency virus (HIV), human T-cell leukemia virus type 1 (HTLV-1), Kaposi’s sarcoma-associated herpesvirus (KSHV), human cytomegalovirus (HCMV), hepatitis B virus (HBV), hepatitis C virus (HCV), and human papillomavirus (HPV)—in the development of haematological malignancies. These viruses are shown to drive tumorigenesis through mechanisms, such as metabolic reprogramming, epigenetic modifications, and remodeling of the immune microenvironment. By directly disrupting fundamental cellular functions and altering metabolic and epigenetic pathways, these viruses foster an immune milieu that supports both viral persistence and tumor growth. A thorough understanding of these viral oncogenic processes is crucial not only for etiological discovery but also for developing targeted interventions. This review emphasizes the need for continued research into the specific ways these viruses manipulate the host cell’s metabolic and epigenetic environments, aiming to provide insights that could guide future advancements in treatment modalities.